Physical Activity in Adolescents Living in Rural and Urban New Caledonia: The Role of Socioenvironmental Factors and the Association With Weight Status - Wattelez, Guillaume; Frayon, Stéphane; Caillaud, Corinne; Galy, Olivier (Frontiers in Public Health, 2021)
Physical activity (PA) is an important factor for the prevention of overweight and obesity particularly during adolescence. This study focuses on the understudied adolescent of New Caledonia with the aim to (1) determine daily PA levels and estimate sedentary time through out-of-school sitting time; (2) highlight the influence of socio-demographic and environmental factors and (3) assess associations of PA and sitting time with overweight and obesity. A sample of 508 school-going adolescents living in New Caledonia was surveyed about their PA habits with the “International Physical Activity Questionnaire” as well as the context in which they usually engage in PA. The influence of the place of living and ethnic community was also investigated. Results indicate that about 66% of adolescents performed at least 60 min of PA daily. Both Melanesian adolescent boys and girls were more active than Caucasian adolescents but only when they lived in rural areas (Female: 115 vs 93 min/day, p = 0.018; Male: 133 vs 97 min/day, p = 0.018). Indeed PA was reduced in urban environment (Female: 88 min/day; Male: 95 min/day, p = 0.028 (rural vs urban in Melanesian adolescents)). Melanesian adolescents also spent less out-of-school sitting time than Caucasian adolescents independently of where they lived (Female: 164 vs 295 min/day, p < 0.001; Male: 167 vs 239 min/day, p = 0.001). For adolescents, feeling safe was positively associated with PA levels (Females: ORadj = 2.58, p = 0.001; Males: ORadj = 4.21, p < 0.001). In adolescent boys, accessibility to a suitable place was also identified as an important factor (ORadj = 2.98, p = 0.004). Finally, while PA and sitting time were negatively associated with overweight in male adolescents (ORadj = 0.28, p = 0.044 and ORadj = 0.39, p = 0.004), they were not in females. Living in a rural area allowed Melanesian adolescents to maintain a more active lifestyle with more physically activities and less sitting time. Our results also indicate that safety is an important driver for engagement in PA. The urban environment in New Caledonia appears to be a contributor of a less active lifestyle in adolescents.